2014
DOI: 10.4161/21688362.2014.969100
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial adhesion molecules and the regulation of intestinal homeostasis during neutrophil transepithelial migration

Abstract: Epithelial adhesion molecules play essential roles in regulating cellular function and maintaining mucosal tissue homeostasis. Some form epithelial junctional complexes to provide structural support for epithelial monolayers and act as a selectively permeable barrier separating luminal contents from the surrounding tissue. Others serve as docking structures for invading viruses and bacteria, while also regulating the immune response. They can either obstruct or serve as footholds for the immune cells recruited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 160 publications
0
29
0
Order By: Relevance
“…Neutrophil (polymorphonuclear leukocyte, PMN) accumulation on the luminal side of intestinal epithelia, termed the crypt abscess, is one of the pathological hallmarks of inflammatory intestinal disease 94 . PMN migration into and across intestinal epithelia is a result of an orchestrated series of steps and the interplay of numerous cell types.…”
Section: Epithelial Endpoint Responses To Cytokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Neutrophil (polymorphonuclear leukocyte, PMN) accumulation on the luminal side of intestinal epithelia, termed the crypt abscess, is one of the pathological hallmarks of inflammatory intestinal disease 94 . PMN migration into and across intestinal epithelia is a result of an orchestrated series of steps and the interplay of numerous cell types.…”
Section: Epithelial Endpoint Responses To Cytokinesmentioning
confidence: 99%
“…It is now appreciated that adhesion-based interactions, involving specific cell adhesion epitopes, are the primary means by which PMNs interact with epithelial cells 94 . For example, initial adhesion events between PMN and epithelia are dependent on PMN β integrins 100 .…”
Section: Epithelial Endpoint Responses To Cytokinesmentioning
confidence: 99%
“…It has been reported that ICAM-1 is an important adhesion molecule belonging to the immunoglobulin superfamily. ICAM-1 is involved in neutrophil chemotaxis by binding with the surface ligand CD11/CD18 on neutrophils and lymphocytes (Dominguez et al, 2015;Liu et al, 2015;Sumagin and Parkos, 2015). MIP-2 belongs to the chemokine C-X-C subfamily and induces marked chemotaxis in neutrophils and lymphocytes (Takahashi et al, 2009;Tateno et al, 2013;Vagima et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The main sources of ATP turns out to be neutrophils, platelets and endothelial cells, thus making connections to innate immune cells (see the above Sumagin reference). 12 It is noteworthy that epithelial barrier protective pathways driven by HIF1a tend not to be the classical regulators of barrier function, such as the tight junction proteins. Rather, HIFregulated pathways control overall tissue integrity.…”
mentioning
confidence: 99%
“…In the next article Sumagin and Parkos provide a comprehensive review of the mechanisms underlying neutrophil migration across mucosal barrier in the context of inflammatory bowel diseases. 12 The authors focus on the role of epithelial expressed adhesion molecules in this process. Notably, neutrophils exit the blood vessel in an apical to basolateral direction, whereas neutrophils travel in the opposite direction, basolateral to apical route, to cross the epithelial barrier.…”
mentioning
confidence: 99%